Distinguishing neurosarcoidosis from multiple sclerosis based on CSF analysis: A retrospective study. (16th June 2020) - Arun, Tarunya; Pattison, Laura; Palace, Jacqueline
Abstract : Objective: To characterize a cohort of patients with neurosarcoidosis with particular focus on CSF analysis and to investigate whether CSF values could help in distinguishing it from multiple sclerosis (MS). Methods: This retrospective cohort study enrolled 85 patients with a diagnosis of neurosarcoidosis (possible, probable, or definite). CSF total protein, white cell count, and angiotensin-converting enzyme levels were measured. CSF and serum oligoclonal immunoglobulin G (IgG) patterns were analyzed with the use of odds ratios and binary logistic regression. Results: Eighty patients had a probable (nonneural positive histology) or definite (neural positive histology) diagnosis of neurosarcoidosis. Most frequent findings on MRI were leptomeningeal enhancement (35%) and white matter and spinal cord involvement (30% and 23%). PET scan showed avid areas in 74% of cases. CSF analysis frequently showed lymphocytosis (63%) and elevated protein (62%), but CSF-selective oligoclonal bands were rare (3%). Serum ACE levels were elevated in 51% of patients but in only 14% of those with isolated neurosarcoidosis. Elevated CSF ACE was not found in any patient. Conclusions: Large elevations in total protein, white cell count, and serum ACE occur in neurosarcoidosis but are rare in MS. The diagnostic use of these tests is, however, limited because minimal changes may occur in both. MS clinical mimics in neurosarcoidosis are not common, and intrathecal synthesis of oligoclonal IgG is a powerful discriminator because it is rare in neurosarcoidosis but occurs in 95% to 98% cases of MS. We suggest caution in making a diagnosis of neurosarcoidosis when intrathecal oligoclonal IgG synthesis is found.